The work of a children's psychiatric clinic in the context of the COVID-19 pandemic in russia. (13th April 2021) - Dovbysh, D.; Bebchuk, M.; Zhorina, Y.; Gimranova, E.; Timoshenko, S.; Popil, E.
Abstract : Introduction: In the context of the Covid-19 pandemic, healthcare workers experienced significant distress. At the same time, concern for the safety and well-being of employees remained important priorities to ensure the quality of care for children with mental illness. Objectives: To study the specifics of the experience of the Covid-19 pandemic among employees of a children's psychiatric clinic, highlight the existing among them attitudes about the pandemic and form administrative decisions to improve the quality of care for children. Methods: 380 employees voluntarily took part in the study (group 1 (G1): 115 people who worked directly with Covid-19 and group 2 (G2): 265 people without this experience) from 05/18/2020 to 05/20/2020. The author's questionnaire included the following blocks: 1) attitude towards patients and colleagues; 2) emotional experiences; 3) ways of coping; 4) social support; 4) finance. Results: The main motive when deciding to work with Covid-19 was the motive of professional duty (25.4% of participants). There are a number of significant differences between group 1 and group 2: participants in G1 are characterized by denial of special experiences associated with Covid-19, seeking help from colleagues in difficult working conditions, reliance on family members and a positive vision of administrative decisions significantly more than participants G2. Relatives of G1 participants are less concerned about their future and health. Conclusions: The personnel decisions made on the basis of the research allowed the clinic's team to provide quality care to children and families throughout the pandemic.